Great imitator-syphilis - Jalal, Fousiya; Oomen, Rachel; Legha, R.; Rasheed, Ashik Abdul; Natarajan, Arunraj Chandravally (International Journal of Research in Medical Sciences, 2024)
An 18-year-old male with no significant comorbidities presented with pain and swelling in multiple small and large joints of the upper and lower limbs, along with pain and redness in both eyes for the past two weeks. He also exhibited hyperpigmented rashes on the palms and soles and had bilateral inguinal lymphadenopathy. Investigations revealed elevated inflammatory markers and a positive ANA on indirect immunofluorescence. An ophthalmology evaluation indicated panuveitis. Subsequently, a VDRL test was performed, which returned reactive, and the TPHA was positive, while the ANA profile was negative. The patient was treated with benzathine penicillin, leading to significant improvement in his arthralgia and rashes.